Implementation of Management Decisions for the Implementation of Blockchain Technologies in Public Authorities - Dziundziuk, Viacheslav; Dziundziuk, Boris (Theory and Practice of Public Administration, 2022)
In recent years, there has been growing interest in blockchain-based operating systems from computer science, economics, and law, but the literature is still in its infancy. The public sector is becoming an area of application for blockchain technology, with governments and others having published more than 200 examples of its use worldwide. However, despite the growing interest, actual implementation of blockchain-based technologies and systems in public administration remains limited. Previous studies have highlighted a number of challenges associated with its implementation, including inadequate regulation, security and privacy issues, lack of interoperable infrastructure, inefficient and energy-intensive transactions, the need for changes in administrative processes, and ultimately, the lack of effective governance models. The purpose of this paper is to identify what management decisions need to be made for the development of blockchain technologies and systems in public authorities and how different contextual factors in public sector affect the available options for blockchain governance. The literature review showed that managerial decisions regarding the use of blockchain in public institutions need to be defined at different levels. At the same time, all these levels are not independent levels of blockchain management, but interrelated ones. It was defined, that blockchain governance in public authorities includes different solutions related to decision mechanisms, incentive mechanisms, consensus building mechanisms, organization, accountability, and management control. Several important conclusions were drawn for system developers and decision makers interested in applying blockchain solutions in public administration. First, politicians and system developers need to consider the interrelationships between levels of public administration and assess the impact of decisions at one level on other levels of public administration. Second, the state current frameworks in a particular sector (e.g., health, security, education, etc.) may influence the choice of a particular blockchain-based governance option. Third, the implementation of blockchain-based systems and technologies in public administration depends on the level of public trust in government. Therefore, further research is needed to clarify the relationship between trust in public institutions and the political choice to build a blockchain-based governance structure.